2006
DOI: 10.1007/s11270-006-9098-x
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Losses in Overland Flow from Cattle, Deer and Sheep Dung

Abstract: The loss of contaminants (phosphorus, nitrogen, sediment and faecal bacteria) in overland flow represents a risk to surface water quality. This study examined the loss of contaminants in overland flow after application of cattle, deer and sheep dung at an equivalent stocking rate (15 su ha −1 ) to field plots. After 1, 3, 7, 12, 19 and 30 days three replicate intact samples of the control and each dung treatment were excavated using a cutting blade (100 cm long ×20 cm wide ×10 cm deep), placed into boxes and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…The risk of loss of dung-P depends on stock type (usually cattle>deer>sheep) and stocking rate (i.e., number of dung deposits) and decreases with time since deposition due to the gradual formation of a crust that prevents the interaction of runoff with the bulk of the dung beneath (McDowell 2006). A similar decrease with time occurs for mineral fertilizers (Austin et al 1996;Nash et al 2000), depending on solubility (as discussed above).…”
Section: Control a Diversity Of Sources Of P In Pasture-based Systemsmentioning
confidence: 93%
“…The risk of loss of dung-P depends on stock type (usually cattle>deer>sheep) and stocking rate (i.e., number of dung deposits) and decreases with time since deposition due to the gradual formation of a crust that prevents the interaction of runoff with the bulk of the dung beneath (McDowell 2006). A similar decrease with time occurs for mineral fertilizers (Austin et al 1996;Nash et al 2000), depending on solubility (as discussed above).…”
Section: Control a Diversity Of Sources Of P In Pasture-based Systemsmentioning
confidence: 93%
“…There was excellent agreement for all the predictions except for P in surface runoff at Hf (Table 10). This large concentration of P during surface runoff probably arose from the large amount of freshly deposited dung present and plant leakage as a result of grazing intensity (McDowell 2006), and equations were not developed or validated for runoff.…”
Section: Leaching Losses For the Paddocks Measured In Seepage Zonesmentioning
confidence: 99%
“…While there is significant evidence of the direct impact of cattle on rural waterways (6,9,11,31), sheep have nevertheless been implicated as contributors to bacterial indicator and pathogen loadings in rivers and streams (8,10,18,20). It has been suggested that the total number of Escherichia coli per hectare of pasture are higher for sheep than for cattle (30).…”
mentioning
confidence: 99%